UTILISING A SOLAR ENERGY CALCULATOR FOR EFFECTIVE SOLAR ENERGY PLANNING AND EQUIPMENT SIZING - Kamran Ali; Adnan Sami Khan; Dr. Jawaid Iqbal (Spectrum of Engineering Sciences, 2025)
The Solar Energy Calculator project is a groundbreaking initiative that makes use of technology to encourage the use of sustainable energy sources. By harnessing a suite of web development technologies, including HTML, CSS, JavaScript, PHP, and MySQL, this initiative has given rise to a cutting-edge tool for estimating solar energy production. The user interface design prioritizes accessibility and user-friendliness, incorporating features such as visual cues and intuitive input forms. The seamless integration of geographic and environmental data into a robust MySQL database ensures the precision of solar energy predictions. The thorough system testing process, which includes a variety of testing forms and constant monitoring of important indicators, has acted as a measure for the system's dependability and quality. This initiative is a demonstration of technology’s transformational potential in tackling urgent environmental issues and fostering a more sustainable future. With global energy demands on the rise and a growing imperative to transition towards renewable energy sources, the Solar Energy Calculator emerges as a timely and essential tool. It empowers users to make informed decisions regarding solar energy adoption, fostering a cleaner and more sustainable energy landscape. The Solar Energy Calculator reflects a dedication to environmental stewardship and a brighter future in addition to being a cutting-edge technology advancement.